1985
DOI: 10.1093/oxfordjournals.aje.a114172
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Zoonotic Toxocariasis in the United States: 1971–1973

Abstract: Demographic characteristics associated with human Toxocara canis infection in children aged one to 11 years were investigated using data from the Health and Nutrition Examination Survey of 1971 to 1973. An enzyme-linked immunosorbent assay with larval stage antigen was used to measure the concentration of antibodies to T. canis in 1,409 available sera. From 4.6 to 7.3% of the children in different geographic regions of the United States have been infected, with serologic prevalence approaching 30% among black … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 9 publications
4
38
1
1
Order By: Relevance
“…Male gender, for example, was suggested to be associated with both increased [27][28][29][30] and decreased 31 risk of infection, with some large studies showing no association between gender and risk. [32][33][34] Young age, 35 low socioeconomic status, 36 low parental education, 34,37 and poor sanitation 6 are additional factors contributing to Toxocara exposure in some communities. Dog ownership has been identified as a risk factor in several 11,27,35,[37][38][39] although not all 40 studies of urban and rural populations.…”
Section: Discussionmentioning
confidence: 99%
“…Male gender, for example, was suggested to be associated with both increased [27][28][29][30] and decreased 31 risk of infection, with some large studies showing no association between gender and risk. [32][33][34] Young age, 35 low socioeconomic status, 36 low parental education, 34,37 and poor sanitation 6 are additional factors contributing to Toxocara exposure in some communities. Dog ownership has been identified as a risk factor in several 11,27,35,[37][38][39] although not all 40 studies of urban and rural populations.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of Toxocara infection as measured by evaluating anti-Toxocara antibodies in serum is variable, with higher prevalence observed in developing countries [1][2][3][4] . Some studies have demonstrated a positive correlation between the presence of anti-Toxocara antibodies and geophagy, onycophagy, a poor hygiene profile and contact with dogs [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, serological evidence of infection was found in 86% of the children in a community of the Caribbean island of St Lucia [17], in 20-35% of urban slum dwellers and Indians of Venezuela [18] and in 62% of the children of Bali (Indonesia) [19]. In studies of children having poor hygiene and sanitation conditions in the US, seroprevalence ranged from 30% to 50% [20,21].…”
mentioning
confidence: 99%